GAYA BAHASA DALAM ANTOLOGI CERPEN CINTA DI ATAS PERAHU CADIK KARYA SENO GUMIRA AJI DHARMA - Ummamah ainun Jariyah, Binti (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study aimed to describe the stylistic comparisons and contradictions in the short story anthology â€œCinta di Atas Perahu Cadikâ€. To determine the style of the language in the short story anthology â€œCinta di Atas Perahu Cadikâ€ which consists of fifteen short stories, researchers studying style by using the theory of Henry Guntur Tarigan. In accordance with the objectives to be achieved in this study, the research approach used is descriptive qualitative approach. Having done the research study style in the short story "Cinta di Atas Perahu Cadik", obtained some results, namely: (1) There are stylistic comparisons that include; style imagery, stylistic metaphor, personification of style and stylistic antithesis . The language is used to provide a description of the author, and foster a sense of beauty of the story. (2) There is a style conflict which include; style stylistic hyperbole and irony. The style of language used by the author to put pressure on the disputed words.